Samsung SmartTV application development (Wiley, 2013)
Take your apps from the small screen to the big screen and start developing for the Samsung SmartTV now! Samsung's SmartTV platform gives developers the opportunity to bring the app experience to the world of home entertainment, creating a more interactive and engaging way to reach their audience. If you're ready to expand your app development skills beyond the mobile environment, look no further than Samsung SmartTV Application Development. This unique guide shows you how to incorporate SmartTV features like Smart Interaction, gesture and voice recognition, and personalized recommendations.